Prebiopsy localization of nonpalpable breast lesions - Junkermann, Hans; Fournier, Dietrich von (Radiological Diagnosis of Breast Diseases, 1997)
The increasing use of mammography for screening is leading to the detection of an increasing number of nonpalpable malignant and bening breast lesions. An excision for diagnostic or therapeutic reasons is necessary if further workup does not exclude malignancy. The ratio between benign and malignant results of biopsies on nonpalpable breast lesions is very variable. It depends not only on the expertise of the radiologist but also on the organization of the decision making (individual decision versus joint decision; Aitken et al. 1992) and especially on the availability of fine-needle or core biopsy(Svane et al. 1993). In the United Ststes, malpractice-related concerns also may affect some decisions concerning biopsy.